Association of maternal physical status and pregnancy outcome - Tiwari, Namrata; Mishra, Vinay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Lots of research both in India and abroad studying the effect of maternal physical markers on their infant’s birth weight is going on. The present study has been planned to evaluate the effects of maternal physical markers on their infant’s anthropometry and cord blood haemoglobin. Methods: Maternal background information, height, last known pre-pregnancy weight, gestational age and number of children was obtained and recorded in case proforma. 100 post-partum women and their newborns were studied. The study was carried in a post-natal ward of a tertiary care hospital. Maternal and neonatal data were recorded. Results: Maternal physical status (pre-pregnancy weight, height and BMI) significantly influences the pregnancy outcome (neonatal parameters) of the baby. Conclusions: There should be emphasis on improvement in nutrition of the girl child to improve the health of the upcoming generations. Maternal body mass index needs to be optimized to reduce perinatal complications to both mother and the baby.